SARS‐CoV‐2‐specific humoral and cellular immunity persists through 9 months irrespective of COVID‐19 severity at hospitalisation. Issue 7 (5th July 2021) - Sandberg, John Tyler; Varnaitė, Renata; Christ, Wanda; Chen, Puran; Muvva, Jagadeeswara R; Maleki, Kimia T; García, Marina; Dzidic, Majda; Folkesson, Elin; Skagerberg, Magdalena; Ahlén, Gustaf; Frelin, Lars; et al.
Abstract: Objectives: Humoral and cellular immunity to SARS‐CoV‐2 following COVID‐19 will likely contribute to protection from reinfection or severe disease. It is therefore important to characterise the initiation and persistence of adaptive immunity to SARS‐CoV‐2 amidst the ongoing pandemic. Methods: Here, we conducted a longitudinal study on hospitalised moderate and severe COVID‐19 patients from the acute phase of disease into convalescence at 5 and 9 months post‐symptom onset. Utilising flow cytometry, serological assays as well as B cell and T cell FluoroSpot assays, we assessed the magnitude and specificity of humoral and cellular immune responses during and after human SARS‐CoV‐2 infection. Results: During acute COVID‐19, we observed an increase in germinal centre activity, a substantial expansion of antibody‐secreting cells and the generation of SARS‐CoV‐2‐neutralising antibodies. Despite gradually decreasing antibody levels, we show persistent, neutralising antibody titres as well as robust specific memory B cell responses and polyfunctional T cell responses at 5 and 9 months after symptom onset in both moderate and severe COVID‐19 patients. Conclusion: Our findings describe the initiation and, importantly, persistence of cellular and humoral SARS‐CoV‐2‐specific immunological memory in hospitalised COVID‐19 patients long after recovery, likely contributing towards protection against reinfection. Abstract : This is a longitudinal study on hospitalised moderate and severe COVID‐19 patients from the acute phase of disease into convalescence at 5 and 9 months post‐symptom onset. During acute COVID‐19, we observed an increase in germinal centre activity, a substantial expansion of antibody‐secreting cells and the generation of SARS‐CoV‐2‐neutralising antibodies. Despite gradually decreasing antibody levels, we show persistent, neutralising antibody titres as well as robust specific memory B cell responses and polyfunctional T cell responses at 5 and 9 months after symptom onset in both moderate and severe COVID‐19 patients.